2009
DOI: 10.1177/000313480907500107
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus Open Total Mesorectal Excision: A Nonrandomized Comparative Prospective Trial in a Tertiary Center in Mexico City

Abstract: Because definitive long-term results are not yet available, the oncologic safety of laparoscopic surgery in rectal cancer remains controversial. Laparoscopic total mesorectal excision (LTME) for rectal cancer has been proposed to have several short-term advantages in comparison with open total mesorectal excision (OTME). However, few prospective randomized studies have been performed. The main purpose of our study was to evaluate whether relevant differences in safety and efficacy exist after elective LTME for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…An additional problem associated with the use of laparoscopic surgery for the lymph nodes, length of specimen and surgical margins) did not differ significantly between those who underwent laparoscopic surgery and those who underwent open resection, in the present study. This finding is supported by randomized trials that demonstrated an equal or greater extent of resection in laparoscopic surgery 10,22 and suggests that oncological treatment principles are not compromised by laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 70%
“…An additional problem associated with the use of laparoscopic surgery for the lymph nodes, length of specimen and surgical margins) did not differ significantly between those who underwent laparoscopic surgery and those who underwent open resection, in the present study. This finding is supported by randomized trials that demonstrated an equal or greater extent of resection in laparoscopic surgery 10,22 and suggests that oncological treatment principles are not compromised by laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 70%
“…From the 253 titles identified through the primary search, 71 were excluded following abstract review. A further 85 studies were then excluded following full‐text review, leaving a total of 97 studies eligible for inclusion in the study and which went on to data extraction and analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective comparative study including 56 patients, Gonzalez et al (González et al, 2009) :10.31557/APJCP.2021.22.12.3967 Propensity Score-Matched Lap vs Open (Ströhlein et al, 2008). Besides, fewer LNs were reported to be associated with a short surgical specimen length and neoadjuvant treatment in rectal cancer patients (Stracci et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that laparoscopic surgery could achieve the same effectiveness as open surgery concerning LN harvesting (Wu et al, 2012;Lujan et al, 2013;Zhou et al, 2015;Stracci et al, 2016;Balducci et al, 2017). Two studies reported greater LN harvesting using the LR approach compared to the OR approach (González et al, 2009;Boutros et al, 2013). In a retrospective comparative study involving (range, 8-18) following TME.…”
Section: Discussionmentioning
confidence: 99%